2018
DOI: 10.1016/j.tcm.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Plant-based diets and cardiovascular health

Abstract: Plant-based diets, defined in terms of low frequency of animal food consumption, have been increasingly recommended for their health benefits. Numerous studies have found plant-based diets, especially when rich in high quality plant foods such as whole grains, fruits, vegetables, and nuts, to be associated with lower risk of cardiovascular outcomes and intermediate risk factors. This review summarizes the current evidence base examining the associations of plant-based diets with cardiovascular endpoints, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
195
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(228 citation statements)
references
References 62 publications
4
195
0
10
Order By: Relevance
“…Our result is in line with earlier meta-analysis data on RCT's related to the effects of plant-based diets on lipoprotein profile [14,15] as well as what has been observed in vegans [25]. Overall, our results support epidemiological findings on a decreased risk of CVD associated with plant protein intake e.g., [26], which thus can be explained by the changes in the composition of whole diet and not by protein per se.…”
Section: Discussionsupporting
confidence: 92%
“…Our result is in line with earlier meta-analysis data on RCT's related to the effects of plant-based diets on lipoprotein profile [14,15] as well as what has been observed in vegans [25]. Overall, our results support epidemiological findings on a decreased risk of CVD associated with plant protein intake e.g., [26], which thus can be explained by the changes in the composition of whole diet and not by protein per se.…”
Section: Discussionsupporting
confidence: 92%
“…The Institute of Medicine has established that the consumption of 200 g of fresh uvaia can provide around 40% of dietary reference intake of total fiber . Recent studies have demonstrated that the consumption of fiber decreases the risk of developing cardiovascular disease and has a beneficial effect on cholesterol levels …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the DASH diet was found to significantly lower systolic and diastolic blood pressure, TC, and LDL-C with no significant effect on HDL-C or triglycerides (TG) [99]. Although the DASH dietary pattern is a well-accepted nutritional approach associated with CVD benefits, new studies should be conducted in order to estimate and confirm its positive effect in clinical practice [6,99].…”
Section: The Dash Dietmentioning
confidence: 99%